UAV indoor localization fusing IMU UWB and optical flow sensor - Liu, Haoran (Nanyang Technological University, 2022)
In the past, limited by the accuracy of indoor localization technology, UAVs were mainly used in outdoor environment with GPS signal. With the increasing demand for UAVs in indoor rescue, surveillance, and performance missions, the research on UAV indoor localization technology has become important. In recent years, UWB equipment has developed rapidly and has become a suitable substitute for GPS due to its advantages of high localization accuracy, large data transmission capacity and strong obstacle penetration ability. However, its robustness is poor so that the appearance of outliers in use is inevitable.